Olhares eurocêntricos: a figura do cigano nas narrativas da série " O povo cigano no Brasil " e das obras " Memórias de um sargento de Milícias " e " Tocaia grande : a face obscura ". - Giassi, Reginaldo Paulo (2014)
This dissertation presented to the Graduate Program in Language Sciences from the University of Southern Santa Catarina, will be analyzed critically within a contemporary perspective which is the representation that builds gypsies from the series O povo cigano no Brasil (2011), developed by the National Senate Radio, based on the episodes Os nômades do sul: vida cigana em Santa Catarina and Os ciganos em São Paulo: as linhas do futuro e a herança do passado. Also, it will seek to understand the extent to which sociocultural values covered by these narratives resemble pejorative descriptions found in the works of Memórias de um sargento de milícias (1852) by Manuel Antonio Almeida (1831-1861) and Tocaia grande: a face obscura (1984) by Jorge Leal Amado de Faria (1912-2001). For this purpose will be used concepts like hybridity, national identity and eurocentrism, that together form the pillars of this research and also contribute effectively to transpire because today there is the perpetuation of a prejudiced and defamatory language rooted in the minds of non-gypsies in opposed to gypsies.